In an A.P., $ {m^{th}} $ term is n and $ {n^{th}} $ term is m, show that its $ {r^{th}} $ term is $ (m + n - r). $
Answer
Verified
408.6k+ views
Hint: An Arithmetic Progression (AP) is the sequence of numbers in which the difference of two successive numbers is always constant.
The standard formula for Arithmetic Progression is: $ {a_n} = a + (n - 1)d $
Where $ {t_n} = $ nth term in the AP
$ a = $ First term of AP
$ d = $ Common difference in the series
$ n = $ Number of terms in the AP
Here, will place $ {m^{th}} $ term is equal to n and $ {n^{th}} $ term is equal to m
Complete step-by-step answer:
Now, take the standard formula and find $ {m^{th}} $ term and $ {n^{th}} $ term
$ {a_m} = a + (m - 1)d $
Given that - $ {a_m} = n $
Place in the above equation –
$ n = a + (m - 1)d $ …… (A)
Similarly, $ {a_n} = a + (n - 1)d $
Given that - $ {a_n} = m $
Place in the above equation –
$ m = a + (n - 1)d $ …… (B)
Subtract equation (B) from the equation (A)
$ n - m = a + (m - 1)d - [a + (n - 1)d] $
When there is a negative sign outside the bracket then the sign of the terms inside the brackets changes. Positive term changes to negative and vice-versa.
$ n - m = a + md - d - a - nd + d $
Combine the like terms in the above expression –
$ n - m = a - a - d + d + md - nd $
Like terms with the same value and the opposite sign cancels each other.
$ n - m = md - nd $
Find the common multiple –
$ n - m = - d(n - m) $
Term multiplicative at one side if moved to the opposite side then it goes in the denominator.
$ \dfrac{{n - m}}{{ - (n - m)}} = d $
Common factors from the numerator and the denominator cancel each other.
$ d = ( - 1) $ …. (C)
Place the above value in the equation (A)
$ n = a + (m - 1)( - 1) $
Simplify the above expression –
$ n = a - m + 1 $
$ a = n + m - 1 $ …. (D)
Now, the rth term of the Arithmetic progression is given by –
$ {a_r} = a + (r - 1)d $
Place the values of equation (C) and (D) in the above equation –
$ {a_r} = n + m - 1 + (r - 1)( - 1) $
Simplify the above expression –
$
{a_r} = n + m - 1 + ( - r + 1) \\
{a_r} = n + m - 1 - r + 1 \;
$
Like terms with the same value and opposite sign cancels each other.
$ {a_r} = m + n - r $
This is the required solution.
Note: Be careful about the sign convention when there is positive term outside the bracket then the sign of the terms inside the bracket remains the same while if there is negative sign outside the bracket then the sign of the terms inside the bracket changes. Positive term changes to negative and negative changes to positive.
The standard formula for Arithmetic Progression is: $ {a_n} = a + (n - 1)d $
Where $ {t_n} = $ nth term in the AP
$ a = $ First term of AP
$ d = $ Common difference in the series
$ n = $ Number of terms in the AP
Here, will place $ {m^{th}} $ term is equal to n and $ {n^{th}} $ term is equal to m
Complete step-by-step answer:
Now, take the standard formula and find $ {m^{th}} $ term and $ {n^{th}} $ term
$ {a_m} = a + (m - 1)d $
Given that - $ {a_m} = n $
Place in the above equation –
$ n = a + (m - 1)d $ …… (A)
Similarly, $ {a_n} = a + (n - 1)d $
Given that - $ {a_n} = m $
Place in the above equation –
$ m = a + (n - 1)d $ …… (B)
Subtract equation (B) from the equation (A)
$ n - m = a + (m - 1)d - [a + (n - 1)d] $
When there is a negative sign outside the bracket then the sign of the terms inside the brackets changes. Positive term changes to negative and vice-versa.
$ n - m = a + md - d - a - nd + d $
Combine the like terms in the above expression –
$ n - m = a - a - d + d + md - nd $
Like terms with the same value and the opposite sign cancels each other.
$ n - m = md - nd $
Find the common multiple –
$ n - m = - d(n - m) $
Term multiplicative at one side if moved to the opposite side then it goes in the denominator.
$ \dfrac{{n - m}}{{ - (n - m)}} = d $
Common factors from the numerator and the denominator cancel each other.
$ d = ( - 1) $ …. (C)
Place the above value in the equation (A)
$ n = a + (m - 1)( - 1) $
Simplify the above expression –
$ n = a - m + 1 $
$ a = n + m - 1 $ …. (D)
Now, the rth term of the Arithmetic progression is given by –
$ {a_r} = a + (r - 1)d $
Place the values of equation (C) and (D) in the above equation –
$ {a_r} = n + m - 1 + (r - 1)( - 1) $
Simplify the above expression –
$
{a_r} = n + m - 1 + ( - r + 1) \\
{a_r} = n + m - 1 - r + 1 \;
$
Like terms with the same value and opposite sign cancels each other.
$ {a_r} = m + n - r $
This is the required solution.
Note: Be careful about the sign convention when there is positive term outside the bracket then the sign of the terms inside the bracket remains the same while if there is negative sign outside the bracket then the sign of the terms inside the bracket changes. Positive term changes to negative and negative changes to positive.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
How do you graph the function fx 4x class 9 maths CBSE
Name the states which share their boundary with Indias class 9 social science CBSE
Difference Between Plant Cell and Animal Cell
What is pollution? How many types of pollution? Define it
What is the color of ferrous sulphate crystals? How does this color change after heating? Name the products formed on strongly heating ferrous sulphate crystals. What type of chemical reaction occurs in this type of change.